Hubungan Intensitas Penggunaan Media Sosial WhatsApp dengan Academic Flow - Baitillah, Nur; Rayaginansih, Syari Fitrah; Thahir, Muthahharah (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to determine the relationship between the intensity of WhatsApp social media use and academic flow in Darul Fatwa High School students in the 2023/2024 school year. The quantitative method of correlational type was used in this study, with a population of 120 students and a sample of 92 students obtained through proportionate stratified random sampling technique. The normality test results show that the significance value on the academic flow variable is 0.200 and the intensity of whatsApp social media use variable is 0.190 which indicates that both variables have normally distributed data. The results of hypothesis testing show a correlation coefficient value of -0.172 with a significance value of 0.100, this value indicates that there is no relationship between variables X and Y.